Accounting for Production Sharing Contracts (PSCs) in the Context of Global Oil Price Uncertainty - Ayu Sapitri; Rina Tjandrakirana DP (Takaza Innovatix Labs Ltd., 2026)
Global oil price volatility disrupts upstream oil and gas stability, complicating Production Sharing Contracts (PSCs) through challenges in accounting treatment, revenue recognition, and asset valuation. This study aims to evaluate PSC accounting concepts and analyze oil price fluctuation impacts on financial reporting. Employing a qualitative Systematic Literature Review (SLR), the population comprises Scopus- and SINTA-indexed journals (2018-2026); the sample includes 20 relevant publications selected via keywords like